Particulate matter 2.5 induced bronchial epithelial cell injury via activation of 5′‐adenosine monophosphate‐activated protein kinase‐mediated autophagy. Issue 3 (11th September 2018) - Long, Fei; Jiang, Hong; Yi, Hongli; Su, Lili; Sun, Jian
Abstract: The impact of particulate matter 2.5 (PM2.5) on the respiratory system is a worldwide concern. However, the mechanisms by which PM2.5 causes disease are still unclear. In this study, we investigated the effect of PM2.5 on autophagy and studied the effect of PM2.5‐induced autophagy and 5′‐adenosine monophosphate‐activated protein kinase (AMPK) on cell proliferation, cell cycle, apoptosis, reactive oxygen species (ROS), and airway inflammation using human bronchial epithelial cells 16HBE140 cells. Results showed that exposure of cells to PM2.5 at a concentration of 100 μg/mL for 24 hours was most effective for inhibiting cell viability. PM2.5 induced cell arrest in the G0/G1 phase and increased mitochondrial membrane potential, ROS, and cell apoptosis with increasing concentration. PM2.5 downregulated cyclin D and matrix metallopeptidase‐9 (MMP‐9) expression but upregulated tissue inhibitor of metalloproteinases‐1 (TIMP‐1) expression, significantly promoted interleukin‐6 (IL‐6), and tumor necrosis factor‐α (TNF‐α) production, and enhanced the level and activation of AMPK. The levels of autophagy‐related protein 5 (ATG5), Beclin‐1, and LC3II/I were significantly increased by PM2.5. The activation of Unc‐51‐like autophagy activating kinase 1 was significantly inhibited by PM2.5. Moreover, ATG5 knockdown inhibited PM2.5‐induced autophagy, ROS, and cell apoptosis significantly. The expression of cyclin D, MMP‐9, and TIMP‐1 was reversed by ATG5 suppression. PM2.5‐induction of IL‐6 and TNF‐α was significantly inhibited by knockdown of ATG5. Thus, inhibition of autophagy protected the cells from PM2.5‐induced injury. PM2.5 induced injury in human bronchial epithelial cells via activation of AMPK‐mediated autophagy, suggesting possible therapeutic targets for the treatment of respiratory diseases. Abstract : This study was aimed to investigate the mechanisms underlying particulate matter 2.5 (PM2.5)‐induced bronchial epithelial cell injury. We found that PM2.5 inhibited cell proliferation, induced cell arrest, and caused early cell apoptosis in 16HBE‐14o human bronchial epithelial cells via activation of 5′‐adenosine monophosphate‐activated protein kinase (AMPK)‐mediated autophagy. Inhibition of autophagy via silencing ATG5 or inhibition of AMPK activation protected PM2.5‐induced cell injury.